Combined benznidazole and pentoxifylline therapy improves behavioral and cognitive changes in association with the regulation of systemic inflammatory profile in chronic experimental Chagas disease - Glaucia Vilar-Pereira; Leda Margarita Castaño-Barrios; Isabela Resende Pereira; Ana Paula da Silva Pinheiro; Thayse do Espírito Santo Protásio da Silva; Lina L. Hernandez-Velasco; Priscila Silva Grijó Farani; Aditi Kulkarni; Sourav Roy; Hílton Antônio Mata dos Santos; Raquel de Oliveira Lopes; Luzineide Wanderley Tinoco; et al. (PLoS ONE, 2025)
Chronically Trypanosoma cruzi -infected mice show signs of behavioral and cognitive changes, resembling aspects of Chagas disease patients. Inflammatory mediators, such as cytokines and nitric oxide (NO) have been linked to mental disorders. Preclinical studies showed the partial effects of the trypanossomicidal drug benznidazole (Bz) on mnemonic alterations. Here, we investigated the participation of the parasite and systemic inflammatory profile in behavioral and cognitive changes, using Bz combined with the immunoregulator pentoxifylline (PTX). Chronically T. cruzi -infected C57BL/6 mice were treated with Bz (25 mg/Kg/day) and PTX (20 mg/Kg/day) as mono or combined therapies, submitted to behavioral tests, and canonical biological stressors were analyzed. Bz therapy had no effects on anxiety, but partially ameliorated innate compulsive behavior, depression, and memory loss, while PTX and, mainly, Bz + PTX had a broader beneficial effect on these changes. Bz and Bz + PTX reduced parasitemia. The three therapies decreased the parasite burden in the brain. Bz and Bz + PTX therapies reduced oxidative stress in the brain tissue, while PTX and Bz + PTX therapies efficiently controlled the elevated concentrations of GABA/glutamate in the cerebral cortex. Even after parasite control, serum concentrations of NO and tumor necrosis factor (TNF) enhanced as the disease progressed. Bz and, mainly, Bz + PTX treatments reduced NO levels. The three therapeutic schemes hamper the progressive increase of TNF levels. Reanalysis of available data on the systemic miRNA transcriptome supports the beneficial role of Bz + PTX therapy on pivotal hubs involved in inflammation of the central nervous system and neurodegenerative disorders. Moreover, principal components analysis (PCA-2D and 3D projections) underlined the distinction between the noninfected and vehicle-treated infected groups, while Bz + PTX-treated infected mice were closer to noninfected controls. The combined Bz + PTX therapy reduced parasite load and regulated pivotal neurochemical changes in the brain and the systemic inflammatory profile, improving behavioral and cognitive changes in a model of Chagas disease.